2020
DOI: 10.3390/biology9050095
|View full text |Cite
|
Sign up to set email alerts
|

3-Iodothyronamine Affects Thermogenic Substrates’ Mobilization in Brown Adipocytes

Abstract: We investigated the effect of 3-iodothyronamine (T1AM) on thermogenic substrates in brown adipocytes (BAs). BAs isolated from the stromal fraction of rat brown adipose tissue were exposed to an adipogenic medium containing insulin in the absence (M) or in the presence of 20 nM T1AM (M+T1AM) for 6 days. At the end of the treatment, the expression of p-PKA/PKA, p-AKT/AKT, p-AMPK/AMPK, p-CREB/CREB, p-P38/P38, type 1 and 3 beta adrenergic receptors (β1–β3AR), GLUT4, type 2 deiodinase (DIO2), and uncoupling protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…The mechanisms underlying the intracellular temperature regulation of cardiomyocytes remain largely unknown. UCPs, particularly UCP1 (which is predominantly expressed in brown adipocytes) have roles in thermogenesis, although a previous study reported that T1AM did not significantly affect the UCP1 expression in brown adipose tissue 25 . Meanwhile, two isoforms (UCP2 and UCP3, but not UCP1) are located in the heart.…”
Section: Discussionmentioning
confidence: 89%
“…The mechanisms underlying the intracellular temperature regulation of cardiomyocytes remain largely unknown. UCPs, particularly UCP1 (which is predominantly expressed in brown adipocytes) have roles in thermogenesis, although a previous study reported that T1AM did not significantly affect the UCP1 expression in brown adipose tissue 25 . Meanwhile, two isoforms (UCP2 and UCP3, but not UCP1) are located in the heart.…”
Section: Discussionmentioning
confidence: 89%
“…We previously demonstrated that UCP-1 protein levels were similar in M + T1AM and M cells [ 17 ]. Instead, in this study, as reported in Figure 3 (panels a and b), the M + TA1 cells showed significantly lower UCP-1 protein expression ( Figure 3 , panel a, b; ** p < 0.01) than the M cells.…”
Section: Resultsmentioning
confidence: 99%
“…The interscapular brown adipose tissue was isolated from one-month-old male Wistar rats (Envigo, San Pietro al Natisone, Italy) according to [ 17 ]. For this study, we received permission from the Ethical Committee for Animal Health (176/2017-PR) from the Italian Ministry of Health, and the experimental procedures were carried on in compliance with the European Convention for the Protection of Vertebrate Animals used for Experimental and Other Scientific Purposes (ETS No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Original Article 3-iodothyronamine inhibits apoptosis induced by myocardial ischemia reperfusion via the Akt/FoxO1 signaling pathway 3-iodothyronamine (T1AM) is an endogenous thyroid hormone derivative with opposing biological effects to those of thyroid hormones (6). Administration of T1AM can lead to a rapid reduction in body temperature, body metabolism (7,8), and heart rate (9). Furthermore, it has therapeutic potential for the treatment of metabolic (10), cardiovascular (11,12), and neurological diseases (13,14).…”
Section: Introductionmentioning
confidence: 99%